Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2024)
We are delighted to present a diverse collection of articles that delve into the intricate relationship between law and technology across various regions and legal landscapes. Our selection covers a wide array of topics, including the impact of information technology on legal practices in Kazakhstan, the adoption of cloud computing for virtual learning environments in Saudi Arabia’s higher education institutions, and a comparative analysis of spectrum management practices between Turkey, Europe, and the United States. Additionally, other articles analyze the classification of cybercrimes in the Gulf Cooperation Council, the evolving legal frameworks surrounding cryptocurrencies in India and Russia, and the role of Pakistani media during the Covid-19 Pandemic. Furthermore, there are articles that investigate the use of Artificial Intelligence in judicial decision-making in Portugal, analyze Colombia’s Artificial Intelligence Strategy, and examine the adoption of virtual annual general meetings by public companies in Nigeria. Comparative studies delve into electronic evidence and expert witness usage in crypto money laundering cases across Indonesia, the United States, and the United Kingdom, as well as legislative approaches to cryptocurrency regulation. Others explore the reform and development of legal frameworks for digitalization, the compliance of Ukrainian legislation with EU regulations on targeted advertising and personal data protection, and the legal implications of Artificial Intelligence in both national and international civil law relations. We also present articles that analyze cyberterrorism in Colombian legislation from a criminology perspective, offer insights from Portuguese case law on contracting additional services in telecommunications, and delve into regulatory asymmetries effects on consumer protection in Brazil.